2016
DOI: 10.1038/srep33031
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bacterial dimethylsulfoniopropionate degradation genes in surface seawater of Arctic Kongsfjorden

Abstract: Dimethylsulfoniopropionate (DMSP), which is the major source of organic sulfur in the world’s oceans, plays a significant role in the global sulfur cycle. This compound is rapidly degraded by marine bacteria either by cleavage to dimethylsulfide (DMS) or demethylation to 3-methylmercaptopropionate (MMPA). The diversity of genes encoding bacterial demethylation (dmdA) and DMS production (dddL and dddP) were measured in Arctic Kongsfjorden. Both dmdA and dddL genes were detected in all stations along a transect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Abundance of members of RCA cluster are often highest during phytoplankton blooms and are mainly found associated with organic and inorganic marine particles/surfaces . Recent studies have shown that members of Sulfitobacter and Loktanella genera prefer particle‐associated lifestyle and are involved in the degradation of dimethylsulfoniopropionate (DMSP) . In the present study, members of SAR116 clade (class Alphaproteobacteria ) were enriched in the PA fractions.…”
Section: Discussionmentioning
confidence: 54%
“…Abundance of members of RCA cluster are often highest during phytoplankton blooms and are mainly found associated with organic and inorganic marine particles/surfaces . Recent studies have shown that members of Sulfitobacter and Loktanella genera prefer particle‐associated lifestyle and are involved in the degradation of dimethylsulfoniopropionate (DMSP) . In the present study, members of SAR116 clade (class Alphaproteobacteria ) were enriched in the PA fractions.…”
Section: Discussionmentioning
confidence: 54%
“…The reason for this shift is unknown, but it may be a consequence of the reduction in the abundance of SAR11 in the sediment and an increase in gamma-proteobacteria such as Pseudomonas containing dddP, or perhaps to the increased DMSP levels experienced in these samples. It was noteworthy that BYSS bacteria predicted to contain dddP, Pseudomonas, Mesorhizobium, and Leisingera, are distinct from previous studies that showed the Roseobacter clade to be the major bacteria possessing dddP (Todd et al, 2009;Varaljay, 2012;Zeng et al, 2016).…”
Section: Byss Sediment Likely Supports Bacteria Cycling Dmsp and Relamentioning
confidence: 70%
“…Class III, DddP), with Zn(II) and Ni(II) ions bound. Zeng et al (2016) investigated the diversity of DMSP dethiomethylase genes in surface water of Kongsfjorden, Svalbard (Bokmål, "the king's fjord"), finding all of the dddL clones were allied to the genus Sulfitobacter. The dddL gene was also identified in Bacteria communities associated to corals (Raina et al 2009).…”
Section: Class I (Dddl) Isoenzymesmentioning
confidence: 99%
“…The dddP gene was found in the genomes of various Alphaproteobacteria and in members of the Ascomycota of the Eukarya, in which functional DMSP dethiomethylase activity was observed (Todd et al 2009). In the Zeng et al (2016) investigation of the diversity of DMSP dethiomethylase genes in surface water of Kongsfjorden, Svalbard, dddP genes were mostly allied to the Rhodobacteraceae, with no specific affiliation to known genera.…”
Section: Class III (Dddp) Isoenzymes and The Reisch-whitman Pathwaymentioning
confidence: 99%
See 1 more Smart Citation